Pengembangan Media Pembelajaran Matematika Tic Tac Toe Berbasis Etnomatematika Pada Materi Bangun Datar SMP Kelas VII - Mevianti, Amanda; Wiratomo, Yogi; Rasyid, H. Harun (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2024)
The purpose of this research is to develop mathematics learning media in the form of games to meet the needs of mathematics learning and can increase the interest and motivation of learning students. The subjects of this study were 33 grade VII students at SMP Negeri 1 Tajurhalang. This research uses a research and development approach by adapting the ADDIE model which includes 5 stages, namely, 1) Analyze, 2) Design, 3) Develop, 4) Implement, and 5) Evaluate. In this study, the product was validated to three material experts and three media experts and carried out individual trials for students. Based on the validation results from experts. The average assessment results from material experts received a score of 4.57 with the criteria of "Very Worthy", and the average assessment results from media experts received a score of 4.13 with the criteria of " Worthy". The results of individual trials get a score of 3.54 with the criteria " Worthy". After validation and revision from experts, a small class trial was carried out for students at SMP Negeri 1 Tajurhalang. The average assessment results from the small class trial scored 3.89 with the criteria " Worthy". The overall results stated that ethnomathematics-based Tic Tac Toe Math learning media were qualified as valid with the criteria " Worthy".